Predictive value of platelet lymphocyte ratio in carbon monoxide poisoning (Annals of Medical Research, 2021)
Aim: Carbon monoxide (CO) poisoning has serious mortality and morbidity among patients who are admitted to the Emergency Department (ED) due to poisoning. Tissue hypoxia and cellular damage, caused by CO poisoning can trigger systemic inflammation. To investigate the relationship between CO poisoning and inflammation, the patient’s Complete Blood Cell (CBC) parameters were compared with carboxyhemoglobin (COHb) levels and outcome.Materials and Methods: Patients who presented with CO poisoning to ED between 01 September 2014 and 01 January 2019 were analyzed. Demographic characteristics (age, gender), laboratory parameters including blood gas analysis, CBC counts, and outcomes of patients were recorded. Inflammatory scores like Neutrophil to Lymphocyte Ratio (NLR), Lymphocyte to Monocyte Ratio (LMR), and Platelet to Lymphocyte Ratio (PLR) were calculated. Patients were divided into 4 groups according to COHb levels as non-toxic, mild, moderate, and severe exposure (30%, respectively).Results: A statistically significant difference was detected between groups regarding lymphocyte level, LMR, and PLR when groups were compared with regard to laboratory values and scores (p values were 0.026, 0.041, and 0.002, respectively). PLR was negatively correlated with COHb level (coefficient -0.212, Sig. 0.017). White blood cell and monocyte levels were found significantly different between patients who were discharged and who received hyperbaric oxygen therapy.Conclusion: CBC parameters may be useful for the clinicians in CO poisoning as in many pathologies due to being rapid, inexpensive, and easily available.
Keywords: Carbon monoxide; Emergency Department; platelet lymphocyte ratio; poisoning